Uncovering the Mechanism of the Xingnaojing Injection against Ischemic Stroke Using a Combined Network Pharmacology Approach and Gut Microbiota Analysis. (20th May 2022) - Liu, Ganlu; Lin, Jingfeng; Zhang, Lina; Gao, Qiang; Wang, Zhenyi; Chang, Ze; Gao, Ying; Ma, Dayong; Han, Zhenyun
Abstract : Objective . To explore the brain protection mechanism of Xingnaojing injection (XNJ) against ischemic stroke (IS) by the network pharmacology approach and gut microbiota analysis. Methods . We used network pharmacology analysis to identify the active components of XNJ and its potential targets against IS and inflammatory bowel disease (IBD) and carried out network analysis, functional annotation, and pathway enrichment analysis. Then, transient middle cerebral artery occlusion (tMCAO) mice model was used to verify the molecular mechanism of XNJ. Results . 36 active compounds were identified from XNJ, and the effect of XNJ against IS was related to the VEGF signaling pathway, NF-kappa B signaling pathway, and gap junction. The effect of XNJ against IBD was related to the T cell receptor signaling pathway, NF-kappa B signaling pathway, and gap junction. In vitro experiments showed that XNJ significantly improved the neurological function of tMCAO mice, reduced the size of cerebral infarction, decreased the permeability of blood-brain barrier (BBB), downregulated the expressions of TLR4, MyD88, and NF-kappa B in the ischemic site, and upregulated the expressions of occludin and ZO-1 in the colon. High-throughput 16S rDNA gene sequencing showed that XNJ upregulated the levels of Akkermansia and downregulated the levels of Flavobacteriaceae, Deferribacteraceae, and Deferribacteres . XNJ increased the concentrations of the short-chain fatty acids (SCFAs) PA (propionate), VA (valerate), IBA (isobutyrate), and IVA (isovalerate) in the feces of the sham germ-free experiment group (SGFEG) mice. Conclusion . IS causes dysbiosis of some specific bacteria in the gut microbiota. XNJ is an effective treatment for IS, and its mechanism was related to improving intestinal barrier function and regulating intestinal flora and SCFAs. Network pharmacology revealed that XNJ acts through multiple targets and multiple pathways.